MEDIASI DALAM PENYELESAIAN SENGKETA PERBANKAN SYARIAH - Emirza Henderlan Harahap; Runtung Runtung; Keizerina Devi Azwar; Utari Maharany Barus (USU LAW JOURNAL, 2014)
ABSTRAK The need of Indonesian Moslem community for the bank operating in accordance with Islamic economic system was not juridically regulated until the enactment of Law No.7/1992 on Banking. In this law, the existence of Islamic bank or syarii banking has not yet been clearly stated, it is only called “bank with shared-revenue principle”. The concept of deliberation and dialogue is then directed to settle the dispute through the principle of legality which is then integrated into the process of proceedings in court through the Regulation of Supreme Court No.2/2003 which has been amended with the Regulation of Supreme Court No.1/2008 on the Procedure of Mediation in Court to make Article 130 HIR/154 RBg on Reconciliation which has been previously available effective. The fact is that reconciliation as stated in Article 130 HIR/154 RBg is currently implemented by the judge as a formality due to several constraints such as the lawyer and the judge are reluctant to peacefully settle the case, the judge has less capability, and peace efforts have not been sufficiently socialized. This condition also impacts the success of the implementation of the Regulation of Supreme Court No.1/2008 integrating mediation into the settlement of case in court, besides the success of the implementation of mediation is very much supported by the regulation that regulates it, facility and infrastructure, and the people involved in it.